2013
DOI: 10.1002/cctc.201300307
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerisation of Propylene Oxide and Carbon Dioxide by Dinuclear Cobalt Porphyrins

Abstract: Two dinuclear cobalt porphyrins comprising different structural tethering motifs at the porphyrin periphery were synthesised, along with a representative mononuclear cobalt porphyrin, and their catalytic activities tested towards carbon dioxide–propylene oxide copolymerisation in the presence of bis(triphenylphosphoranyl)ammonium chloride cocatalyst. The catalytic activities of the mononuclear and the bis‐para‐tethered dinuclear cobalt porphyrin with selective formation of poly(propylene carbonate) are largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 56 publications
1
24
0
2
Order By: Relevance
“…В спектрах ЯМР 1 Н порфиринов 7 и 8 присутствуют сигналы порфи-ринового фрагмента (H β -пиррольных и внутрицикличе-ских NH-протонов) и ароматических заместителей, при-чем соотношение интегральных интенсивностей сиг-налов протонов порфиринового фрагмента и сигналов протонов фенольного фрагмента соответствует одному фенольному фрагменту в молекуле. Строение описанных ранее порфиринов 1-6 подтверждено сопоставлением их спектральных (UV-Vis, ЯМР, масс) характеристик с данными известными из литературы: [23][24][25][26][27] порфирины 1-6 соответствуют заявленной структуре. Спектральные характеристики неописанных ранее порфиринов 7 и 8 аналогичны известным порфиринам 1-6.…”
Section: результаты и их обсуждениеunclassified
“…В спектрах ЯМР 1 Н порфиринов 7 и 8 присутствуют сигналы порфи-ринового фрагмента (H β -пиррольных и внутрицикличе-ских NH-протонов) и ароматических заместителей, при-чем соотношение интегральных интенсивностей сиг-налов протонов порфиринового фрагмента и сигналов протонов фенольного фрагмента соответствует одному фенольному фрагменту в молекуле. Строение описанных ранее порфиринов 1-6 подтверждено сопоставлением их спектральных (UV-Vis, ЯМР, масс) характеристик с данными известными из литературы: [23][24][25][26][27] порфирины 1-6 соответствуют заявленной структуре. Спектральные характеристики неописанных ранее порфиринов 7 и 8 аналогичны известным порфиринам 1-6.…”
Section: результаты и их обсуждениеunclassified
“…As discussed earlier, in many cases, the rationale for these studies is that two metal centres held in close proximity to one another have shown better activity than monometallic counterparts [33,63,77,79,84,85,[141][142][143].…”
Section: Polymer Chain Shuttling Mechanismmentioning
confidence: 99%
“…Moreover, the utilisation of a cocatalyst was found to be essential. One explanation for the poor performance of the bimetallic catalyst is that catalyst deactivation, by reduction of cobalt(III) to cobalt(II), appears faster in the case 18 [143,159]. …”
Section: Linked Bimetallic Porphyrin Catalystsmentioning
confidence: 99%
“…98 9Cobalt bis-porphyrins along with a mono-nuclear cobalt porphyrin have been synthesized and used10 as catalysts for carbon dioxide-propylene oxide copolymerization, showing that the copolymerization 11 was effective in the presence of bis(triphenylphosphoranyl) ammonium chloride cocatalyst 141. 98 9Cobalt bis-porphyrins along with a mono-nuclear cobalt porphyrin have been synthesized and used10 as catalysts for carbon dioxide-propylene oxide copolymerization, showing that the copolymerization 11 was effective in the presence of bis(triphenylphosphoranyl) ammonium chloride cocatalyst 141.…”
mentioning
confidence: 99%